Hands on : Funding the future
In poor and disadvantaged communities people need skills trainining and financial backing. this tape looks at challenge funds which are helping in Brazil and Prostitutes run their own business in Brazil, ex-convicts become gardeners in Zambia and elderly thais run a rubber plantation to fund their retirement.